Fresno County Bar Association Bar Banquet at TorNino's - Watkins, Howard::::::::: (1984)
Dan Whitehurst doing gag jokes as Shecky Greene In background: Bob Fishman on guitar, Hal Bolen on drums, Tom Riche on keyboard, John B. Smith